Association between measured teamwork and medical errors: an observational study of prehospital care in the USA. Issue 10 (31st October 2019) - Herzberg, Simone; Hansen, Matt; Schoonover, Amanda; Skarica, Barbara; McNulty, James; Harrod, Tabria; Snowden, Jonathan M; Lambert, William; Guise, Jeanne-Marie
Abstract : Objectives: The goal of this study was to examine the relationship between measured teamwork and adverse safety events in the prehospital emergency care of children using high-fidelity simulation. We posit that non-technical skills such as leadership, teamwork, situation awareness and decision-making are associated with the clinical success of teams. Design: Observational study. Setting: Emergency medical services (EMS) responders were recruited from public fire and private transport agencies in Oregon State to participate in four simulations of paediatric emergencies using high-fidelity patient simulators, scene design, and professional actors playing parents and bystanders. Participants: Forty-four fire/transport teams consisting of 259 EMS professionals consented to participate and completed simulations. Primary and secondary outcome measures: Teams were assessed using the Clinical Teamwork Scale (CTS), a validated instrument that measures overall teamwork and 15 specific elements in five overarching domains: communication, decision-making, role responsibility (leadership and followership), situational awareness/resource management and patient-friendliness. We used generalised estimating equations to estimate the odds of error with increasing overall CTS teamwork score while adjusting for clinical scenario and potential clustering by team. Results: Across 176 simulations, the mean overall score on the CTS was 6.04 (SD 2.10; range 1=poor to 10=perfect) and was normally distributed. The distribution of scores was similar across the four clinical scenarios. At least one error was observed in 82% of the simulations. In simulations with at least one observed error, the mean CTS score was 5.76 (SD 2.04) compared with 7.16 (SD 1.95) in scenarios with no observed error. Logistic regression analysis accounting for clustering at the team level revealed that the odds of an error decreased 28% with each unit increase in CTS (OR 0.72, 95% CI 0.59 to 0.88). Conclusions: This study found that overall teamwork among care delivery teams was strongly associated with the risk of serious adverse events in simulated scenarios of caring for critically ill and injured children.